Knowledge, Attitudes and Practices Towards Government Order Related to COVID-19 in Public Bus: A Cross-Sectional Study in Bangladesh - Mia, Md Tuhin; Eva, Esrat Jahan; Ahasan, Naima; Mahmud , Hossain; Sikder, Chayon (South Asian Journal of Social Sciences and Humanities, 2025)
Bangladesh currently faces an unavoidable challenge to cope with the COVID-19 pandemic. In response to surging COVID-19 cases, the government has formulated some legal frameworks to be implemented in public bus usage during COVID-19. The study aims to explore the level of Knowledge, Attitudes, and Practices (KAP) among the general people in response to such framework in the public bus of Dhaka city in Bangladesh. This cross sectional study was conducted with 400 participants (public bus passengers, drivers, helpers and owners) using the purposive sampling and semi-structured questionnaire survey over eight months from November 2021 to June 2022. This study illustrates that 100% of respondents are very well-known about the Coronavirus and 81% reported use of public buses during COVID-19 is unsafe where cent percent have been taken more or fewer precautionary steps in using a public bus. Around 30% use masks as a protective measure, of which 30.2% consider it as government order. About 100% of respondents are very well known about government order (directives) but 69.2% not obliged to practice these orders in using public bus where they claimed incognizance of people as a main causal factor of this less practice. About 54.3% of respondents strongly agreed to use masks and maintain distance in public buses where 55% hand sanitization, 60.3% cover face during coughing, and 50% avoid closely seating in public buses. It is observed that there is a significant association between marital status, respondent’s category, knowledge on COVID-19 order and KAP towards government order (directives) of the public bus at 1% level of significance as where p<0.001. Most of the respondents have a good level of knowledge, but they experience poor government orders regarding COVID-19 on the public bus.